A brief dive into the phenomenon of cisplatin resistance in non-small-cell lung cancer - Sobczak, Maciej (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2021)
Lung cancer is one of the most lethal types of cancer due to a lack of proper treatment. The rare presence of molecular therapy targets forces the use of platinum-based drugs. Cisplatin, approved by the USA as an anticancer therapy in the 1970s, is still one of the most prominent therapies against lung cancer. Unfortunately, the biggest limitation of cisplatin-based therapy is the development of cisplatin resistance. Cancer cells overcome the vast DNA damage caused by the drug in a variety of ways such as detoxication and extracellular transport of the drug, enhanced repair mechanisms, omitting apoptosis and epigenetic alterations. Chemotherapy resistance is an issue that so far cannot be dealt with. Nevertheless, better understanding of the molecular pathways behind cisplatin resistance brings hope for better therapy outcomes in lung cancer patients.